REAL-TIME MONITORING OF HIGH-POTENTIAL STEM CELLS AS AN INNOVATIVE BIOLOGICAL ELEMENT IN BIOSENSORS (REMUNOM, 2025)
The convergence between stem cell biotechnology and biosensor technology represents a significant advance for drug screening and regenerative medicine. Embryonic stem cells (ESCs), characterized by their pluripotency and self-renewal capacity, offer a renewable and physiologically relevant cell source for the construction of cell-based biosensors (CBSs). Despite technical challenges related to maintaining cell viability and standardization, the field is advancing toward integrated Lab-on-a-Chip systems and single-cell biosensors, promising to revolutionize high-throughput pharmacology and personalized medicine. In this article, we discuss compatible transduction platforms, such as Microelectrode Arrays (MEAs) and Light-Addressable Potentiometric Sensors (LAPS), and the role of surface nanoengineering in optimizing the cell-transducer interface. Key applications include screening for cardiotoxicity and neurotoxicity of new drugs, real-time monitoring of cell differentiation, and detection of environmental toxicity. This article explores the fundamentals of this integration, highlighting ESCs (or their differentiated derivatives) as biological recognition elements that convert cellular responses to external stimuli into measurable signals.